FEATURES OF TRANSLATION OF LENGTH MEASURES TERMS BETWEEN RUSSIAN AND UZBEK LANGUAGES (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the features of the translation of length measures between the Russian and Uzbek languages, taking into account lexical, semantic, grammatical and cultural factors. A systematic analysis of the main difficulties arising in the transfer of units of measurement in scientific and technical documentation and educational materials is carried out. Both obsolete and modern units of length are considered, translation patterns and variability of lexical equivalents are revealed. The work is based on the study of regulatory documents, specialized dictionaries and practical translation examples, which allows us to formulate recommendations for standardizing terminology and improving the quality of translations. The results of the study will be useful to linguists, translators, specialists in the field of technical documentation and educational materials.